Synthesis of uniformly excited sparse rectangular planar array for sidelobe suppression using multi-objective optimisation algorithm - Zhang, Chengyan; Fu, Xiongjun; Chen, Xu; Peng, Shuilian; Min, Xie (Journal of engineering (Stevenage, England), 2019)
Here, the multi-objective optimisation algorithm speed-constrained multi-objective particle swarm optimisation is applied to the synthesis of uniformly excited sparse-rectangular planar array with low sidelobe level. Numerical simulations have been conducted to test the performance of multi-objective optimisation algorithm when used in this synthesis problem, and resulting radiation patterns are compared with those from other existing synthesis algorithms in literatures. Comparative results illustrate that the proposed algorithm has obtained the lowest maximum sidelobe level (MSLL) in φ = 0 plane (φ is the elevation angle) of radiation pattern combined with the lowest maximum MSLL in φ = π/2 plane. In addition, convergence performance of the multi-objective optimisation algorithm when used in this synthesis problem has also been investigated here.